2016
DOI: 10.1097/yct.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Electroconvulsive Therapy

Abstract: Objective To scrutinize a series of pregnant women treated with electroconvulsive therapy (ECT) at a tertiary treatment center and combine this data with a literature review to refine the treatment guidelines for ECT during pregnancy. Methods A retrospective chart review of mentally ill pregnant patients treated with ECT since the establishment of a formal women’s mental health program. Results A total of eight pregnant women treated with ECT were identified from 01/2012–08/2014. Information was extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Therefore, propofol can be considered as an ideal agent for ECT during pregnancy [5,12]. Meaningfully, recent reports have indicated that propofol has been the most commonly used agent in anesthetic induction in pregnant women undergoing ECT [5,9,13-14]. In a case report by De Asis et al, ECT was applied at the 23rd gestational week in a patient with bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, propofol can be considered as an ideal agent for ECT during pregnancy [5,12]. Meaningfully, recent reports have indicated that propofol has been the most commonly used agent in anesthetic induction in pregnant women undergoing ECT [5,9,13-14]. In a case report by De Asis et al, ECT was applied at the 23rd gestational week in a patient with bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…ECT may be a safe procedure in pregnant patients; however, airway management may not be safe. Airway management is usually provided by a face mask in such cases since the majority of the cases have a low gestational week and a short duration of processing, mainly due to the short duration of the effects of neuromuscular blocking agents used and the early return of spontaneous breathing [5,13-14]. In our study, we used the aspiration measures mentioned above and the patients were ventilated manually with 100% oxygen 3 L/min using a face mask.…”
Section: Discussionmentioning
confidence: 99%
“…48 Although the evidences on effectiveness of ECT in pregnant women are mostly based on the results of case reports and there is no prospective controlled study, results from previous studies indicate that use of ECT is generally safe during the entire period of pregnancy. 49,50 Maternal changes such as decreased utero-placental perfusion, risk of aspiration, compression on aortocaval system during pregnancy and other comorbidities and the possibility of fetal heart rate change may need to be considered, but serious adverse events caused by ECT during pregnancy seem to be uncommon. 51 In a retrospective study, the efficacy and safety of ECT in 33 (n=19 MDD; the rest=bipolar disorder or schizophrenia) pregnant patients were evaluated.…”
Section: Depression In Pregnancy and Postpartum Depressionmentioning
confidence: 99%
“…Several studies discuss precautions to take in pregnant patients, but there are no consistent guidelines for the performance of ECT in pregnancy. [12][13][14] These precautions include left lateral decubitus positioning, IV hydration, use of proton pump inhibitors or H2 blockers, and intubation. Other precautions include performance of a pelvic exam, avoidance of hyperventilation, and some form of fetal monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Other precautions include performance of a pelvic exam, avoidance of hyperventilation, and some form of fetal monitoring. [12][13][14] There is no consistent guideline for fetal monitoring during ECT and no consistent patterns of adverse outcomes. 13 The timing (pre/post ECT) and duration of fetal monitoring are not well described.…”
Section: Introductionmentioning
confidence: 99%